Effects of circular openings in RC deep beams at top of shear span near support - Mohamad Mirzan, Yusof (2014)
Opening is very important in structures in order to allow for the passage of conduits and also for mechanical purposes. There are various shapes of opening available with different dimensions of the openings. The presence of opening in the web can bring advantages in terms of minimizing the cost of the construction, however it may result into many problems which will cause cracking and deflection in the beam. Very limited studies have been done on deep beams with circular web opening. Therefore, this study was conducted in order to study the effects of circular opening due to the different sizes of opening located near the point load. In this study, the sizes of the circular opening considered were 0150 mm, 0200 mm and 0250 mm. All beams of identical cross section of 100 mm x 500 mm and 1200 mm in length with circular opening of different sizes were provided. The beams were tested under four-point bending until failure. The results concern in this study were load deflection behavior, crack pattern and also failure mode. The presence of openings in the beams causes 'a reduction in the strength of the beam. The ultimate load of CB, BCO1, BCO2 and BCO3 were 42.97 kN, 46.59 kN, 30.55 kN and 27.99 kN respectively. Solid control beams and beams with circular openings failed due to shear. Increase in the opening size causes the cracks to be more severe. The increase in the diameter of openings disturb the load path transfer. In addition, providing openings of 0200 mm reduces the strength by 28.90% and openings of 0250 mm decreases the strength of the beam by 34.86%. Therefore, it can be concluded that increasing the size of openings causes a reduction in the strength of the beam.